RELASI SYARIAT ISLAM DAN NEGARA DALAM DIMENSI HUKUM TATA NEGARA INDONESIA - Nasaruddin Umar (TAHKIM, 2017)
This study aims to re-elaborate the relationship pattern between religion and state in dimension of Indonesia State Administration Law at post-amendment of Constitution NRI 1945. With the ratification of Article 31 paragraph 3 and and 5 and Article 28 paragraph 2 of Constitution NRI 1945, has brought a logical consequences on the formation of legislation because the religious values in itself to be the basic law of legislation in Indonesia, thus the relationship between religion and state in Indonesia becomes a new relationship patterns in the structure of Indonesian state administration law. The method used in this research is literature study. The findings of research is the Islamic sharia and state relationship patterns of post-Amendment the the Constitution NRI 1945 is the concentric relationship pattern in which the Islamic sharia values to be the center of considerations and restrictions the enactment of state legal norms that the Islamic sharia values to be the law source of legislation. These relationships pattern will be effective if described into a pyramid hierarchy systems of national legal in the formation of legislation, because without solid relationship at the level of values, principles and articles in the regulation, then constitutional relationship patterns will not effective in maximizing the contribution of Islamic law in national law. Key words: Relations, Islamic Sharia, state, and Atate Administration Law